Case reportClosure of patent ductus arteriosus with oversized Amplatzer occluder in a patient with pulmonary hypertension - Karapinar, Hekim; Kucukdurmaz, Zekeriya; Oflaz, Mehmet Burhan; Gül, İbrahim; Yilmaz, Ahmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Diagnosis of patent ductus arteriosus is rare in adulthood. Closure of ductus is difficult when diagnosed at an adult age due to the development of pulmonary hypertension and pulmonary arterial disease that generally occurs. Closure of the ductus might be contraindicated, as it may lead to deterioration of the pulmonary arterial perfusion or to a pulmonary hypertensive crisis. In addition, another risk associated with percutaneous closure for these patients is the risk of embolism of the asymmetrically shaped device to the systemic circulation. We present in this manuscript a case with patent ductus arteriosus diagnosed at an adult age that underwent successful closure by the percutaneous method. During closure, an oversized Amplatzer duct occluder device was used to reduce the risk of device embolism.